Social Dimensions of Free Trade Agreements. (Studies on growth with equity., 2013)
This report provides a comprehensive review of all existing trade agreements that include social provisions and discusses impacts for enterprises and workers. It also helps assess the challenges for arising from the multiplication of trade agreements that include different social provisions.